Upaya Pengelolaan Tuberkulosis Paru Dalam Kedokteran Keluarga - Aditya Fajar Perkasa; Noviana Zara (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2024)
Tuberculosis (TB) is an infectious disease caused by infection with Mycobacterium tuberculosis complex, which is the most frequently found bacteria and is transmitted between humans via the air route. The incidence of TB in Indonesia in 2020 was 301 per 100,000 population. Therefore, family doctors play an important role in promoting health and preventing TB disease, identifying risk factors, clinical problems, and providing management to patients by implementing holistic family doctor services based on evidence based medicine through a patient centered and family approach, the main problem This patient did not wear PPE when in direct contact with other patients while working at PKM Tanah Pasir. In this case report, primary data was obtained through anamnesis (autoanamnesis), physical examination and home visits to complete family data, psychosocial and environmental data. Patient Mr. R, 45 years old, underwent routine TB treatment at the Tanah Pasir Community Health Center and was diagnosed two months ago. The patient has normal nutritional status. Pharmacological and non-pharmacological interventions are carried out for patients in the form of education about TB disease for patients and their families. The results of the evaluation of the intervention are that the patient has started to do physical activity and the family has supported the patient's routine treatment.